Kombinasi katalis FeSO4 dan H2O2 dalam penanganan air limbah agroindustri kopi menggunakan metode foto Fenton - Novita, Elida; Sudirman, Nurfila Sari; Pradana, Hendra Andiananta; Afriliana, Asma; Harsono, Soni Sisbudi; Purnomo, Bambang Herry; Hartono, Tjahjo (AGROINTEK, 2025)
Wastewater production from the coffee agroindustry is generally brown. Melanoidin contents cause it and the high content of organic matter in coffee processing wastewater can impact water pollution. Turbid coffee processing wastewater can prevent sunlight from entering the water if it is channeled directly into water bodies without prior treatment. The research aims to improve the quality of coffee processing wastewater using the photo Fenton method, which combines catalyst reagents from H2O2 and FeSO4. The stages of the research consist of adjusting the pH of the process, combining H2O2 and FeSO4 dosages, irradiating using UV light, settling, and analyzing wastewater quality improvements with parameters i.e. Total Suspended Solid (TSS), turbidity, color, pH, and Chemicals Oxygen Demand (COD). The research results show that adding H2O2 and FeSO4 treatment in the Fenton photo can improve the quality of coffee processing wastewater. H2F1 treatment (H2O2 0.2 M and FeSO4 0.0015 M) is the best alternative for reducing TSS, turbidity, color, and COD parameters. The percentage reduction values for TSS, turbidity, color, and COD is sequentially 95.55; 98.40; 93.97; and 72.47 %. The combination of H2SO4 and FeSO4 catalysts can be used as an alternative tertiary method for coffee agro-industrial wastewater purification which is effective and efficient.